MiR-206-G6PD axis regulates lipogenesis and cell growth in hepatocellular carcinoma cell. Issue 5 (16th March 2021) - Wang, Ao; Chen, Bocen; Jian, Shaoqin; Cai, Wangwei; Xiao, Man; Du, Guankui
Abstract : Supplemental Digital Content is available in the text. Abstract : miR-206 plays an essential role in repressing the growth of multiple cancer cells. Glucose-6-phosphate dehydrogenase (G6PD) is the rate-limiting enzyme of the pentose phosphate pathway. However, it is mostly unknown whether G6PD is associated with miR-206-mediated growth repression of hepatocellular carcinoma (HCC) cells. In this study, we found that the expression of G6PD was upregulated in HCC patients and cell lines, whereas the expression of miR-206 was negatively associated with the clinical staging criterion of primary liver cancer. Overexpression of G6PD increased lipid accumulation and promoted cell proliferation. Conversely, inhibition of G6PD expression decreased lipid accumulation and suppressed cell proliferation. Moreover, miR-206 could directly bind to G6PD mRNA 3´-UTR and downregulate G6PD level. Overexpression of G6PD significantly attenuated the miR-206 mimic-mediated suppression of lipid accumulation and cell proliferation. In summary, the results demonstrated that miR-206 could inhibit lipid accumulation and growth of HCC cells by targeting G6PD, suggesting that the miR-206-G6PD axis may be a promising target for treating HCC.